Work cognitions and work intentions: a canonical correlation study. Issue 1 (1st January 2021) - Nimon, Kim; Joo, Baek-Kyoo (Brian); Bontrager, Marvin
ABSTRACT: Positive organizational science has emerged during the last two decades in multiple research fields. In support, two positive sets of measures, work cognitions and work intentions, have been developed and applied in the field of human resource development (HRD). The purpose of this study was to examine the multivariate relationship between eight measures of work cognition (i.e., autonomy, collaboration, connectedness with colleagues, connectedness with leaders, distributive fairness, feedback, growth, meaningful work ) and five measures of work intention (i.e., intent to endorse, intent to perform, intent to stay, intent to use discretionary effort, intent to use organizational citizens behaviours ). Results of a canonical correlation analysis (CCA) of 518 employees in a South Korean conglomerate indicated that employees intended to endorse the organization, stay with the organization, and perform better, when they had a higher level of cognitive perceptions on meaningful work and feedback in their job as well as organizational support for their growth. This is an encouraging finding for HRD practitioners as various techniques can be employed to increase employees' positive perceptions about their job and organization. Recommendations are suggested to provide enhanced learning and development opportunities for employees and to redesign their work to be more meaningful and to have better feedback.